Photocurable composition, cured product, and dental product

By using a photocuring composition containing a specific photocuring unit, the problem of difficulty in taking into account both hardness and toughness in use is solved, and the effect of high toughness and appropriate hardness after photocuring is achieved.

JP7662512B2Active Publication Date: 2025-04-15MITSUI CHEMICALS INC

Patent Information

Application Number
JP2021512123
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-29
Filing Date
2020-03-30
Publication Date
2025-04-15
Estimated Expiration
2040-03-30

AI Technical Summary

Technical Problem

The dental cover is difficult to maintain proper hardness and toughness during use, which may cause discomfort when worn in the oral cavity and is prone to damage during long-term use.

Method used

A photocuring composition is employed, which comprises a di(methyl)ate unit having two methyl acid ester oxygen groups and two urea bonds, an acrylate unit having one acryl loyl group, and a photocuring initial.

Benefits of technology

The photocuring composition exhibits a high destructive workload after photocuring, indicating its high toughness while maintaining appropriate bending strength and flexural modulus, ensuring that the tooth cover has both sufficient hardness and no excessive stiffness in use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662512000029
    Figure 0007662512000029
  • Figure 0007662512000030
    Figure 0007662512000030
  • Figure 0007662512000001
    Figure 0007662512000001
Patent Text Reader

Abstract

A photocurable composition comprising a di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds, an acrylic monomer (B) having one acryloyl group, and a photopolymerization initiator; a cured product of the photocurable composition; and a dental product comprising the cured product.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a photocurable composition, a cured product, and a dental product. [Background technology]

[0002] Today, resins are used for a variety of purposes, and different properties are required depending on the purpose. For example, mouth guards used in dentistry are used for the treatment of temporomandibular joint disorders and orthodontic treatment.

[0003] Currently, the most common method for making dental mouthpieces is to soften a resin sheet by heating it in a water bath, press it against a model, mold it, and then photopolymerize or heat-polymerize it. Acrylic resin is mainly used as the resin material for mouthpieces used in dentistry. For example, JP-A-11-79925 discloses in its working examples a photocurable composition for splints that contains a urethane dimethacrylate such as di-2-methacryloxyethyl-2,2,4-trimethylhexamethylene dicarbamate (UDMA), a bifunctional methacrylate that does not have a urethane bond such as 1,3-butylene glycol dimethacrylate, a urethane oligomer, and an inorganic filler such as silica. Summary of the Invention [Problem to be solved by the invention]

[0004] Among dental mouthpieces, splints used for the treatment of temporomandibular joint disorders, mouthpieces used for orthodontic treatment and for preventing teeth grinding, and retainers for maintaining corrected teeth alignment are used to correct or maintain teeth alignment, and therefore require a certain degree of hardness and strength. On the other hand, since they are used in the oral cavity for a long time, if the hardness is too high, it becomes uncomfortable to wear, so it is desirable that the bending strength and bending modulus are not too high. However, if the bending strength and bending modulus are low, it becomes difficult to maintain strength (i.e., toughness), and it is difficult to maintain the hardness within an appropriate range while maintaining strength.

[0005] In addition, as mentioned above, dental mouthpieces are required to have a certain degree of hardness, but if the hardness is too high, it may cause pain or discomfort when used in the oral cavity. This is a serious problem in the field of dentistry. On the other hand, if the hardness is suppressed, it is difficult to maintain high toughness, but if the toughness is not high, it cannot withstand long-term use. In other words, it is desirable to have a hardness in an appropriate range and high toughness, and a resin material that combines higher strength and an appropriate range of hardness is required.

[0006] An object of the present disclosure is to provide a photocurable composition that, after photocuring, can exhibit a high total work of fracture, which is an index of toughness, while maintaining flexural strength and flexural modulus, which are indexes of hardness, in appropriate ranges, and further to provide a cured product of the photocurable composition and a dental product containing the cured product. [Means for solving the problem]

[0007] Means for Solving the Problems The present inventors have conducted intensive studies and have found that a photocurable composition containing a di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds, an acrylic monomer (B) having one acryloyl group, and a photopolymerization initiator has excellent toughness and appropriate ranges of flexural strength and flexural modulus after photocuring, thereby completing the present invention. That is, the specific means for solving the above problems are as follows.

[0008] <1> A photocurable composition comprising: a di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds; an acrylic monomer (B) having one acryloyl group; and a photopolymerization initiator. <2> In the photocurable composition, the ratio of the number of acryloyl groups to the total number of acryloyl groups and methacryloyl groups is 10% or more. <1> The photocurable composition according to claim 1. <3> The cured product obtained by curing the photocurable composition has a flexural strength of 50 to 70 MPa, a flexural modulus of 1500 to 2000 MPa, and a total work of fracture of 250 J / m 2 That's all. <1> or <2> The photocurable composition according to claim 1. <4> The di(meth)acrylic monomer (A) is a compound represented by the following general formula (1): <1> ~ <3> 13. The photocurable composition according to claim 12, [ka] (In formula (1), R 1 is a divalent chain hydrocarbon group, a divalent hydrocarbon group having an aromatic structure, or a divalent hydrocarbon group having an alicyclic structure, R 2 and R 3 each independently represents a divalent chain hydrocarbon group which may have a substituent, R 4 and R 5 are each independently a methyl group or a hydrogen atom.

[0009] <5> In the general formula (1), R 1 is a divalent hydrocarbon group having 6 to 12 carbon atoms and an aromatic structure or a divalent hydrocarbon group having 6 to 12 carbon atoms and an alicyclic structure, R 2 and R 3 are each independently an unsubstituted divalent chain hydrocarbon group having 2 to 6 carbon atoms; <4> The photocurable composition according to claim 1. <6> The acrylic monomer (B) contains at least one of a compound represented by the following general formula (2) and a compound represented by the following general formula (3): <1> ~ <5> 13. The photocurable composition according to claim 12, [ka] (In formula (2), R 6 is a monovalent organic group which may have a ring structure. In formula (3), R 7 and R 8each independently represents a monovalent organic group which may have a ring structure or a hydrogen atom; R 7 and R 8 may be bonded to each other to form a ring. <7> The acrylic monomer (B) contains a compound represented by general formula (2), In the general formula (2), R 6 is a monovalent organic group having a ring structure and having 6 to 20 carbon atoms; <6> The photocurable composition according to claim 1. <8> The weight average molecular weight of the di(meth)acrylic monomer (A) is 380 to 700. <1> ~ <7> 13. The photocurable composition according to claim 12, <9> The weight average molecular weight of the acrylic monomer (B) is 130 to 320. <1> ~ <8> 13. The photocurable composition according to claim 12,

[0010] <10> the content of the di(meth)acrylic monomer (A) is 300 parts by mass or more and 950 parts by mass or less relative to 1000 parts by mass of the total content of the (meth)acrylic monomer components contained in the photocurable composition; <1> ~ <9> 13. The photocurable composition according to claim 12, <11> 11. The photocurable composition according to claim 1, wherein the total content of the di(meth)acrylic monomer (A) and the acrylic monomer (B) is 800 parts by mass or more per 1000 parts by mass of the total content of the (meth)acrylic monomer components contained in the photocurable composition. <12> A photocurable composition comprising a photopolymerizable component and a photopolymerization initiator, The cured product obtained by curing the photocurable composition has a flexural modulus of 1500 MPa to 2500 MPa and a total work of fracture of 250 J / m 2 The above is the photocurable composition. <13> The viscosity measured using an E-type viscometer at 25°C and 50 rpm is 20 mPa·s to 3000 mPa·s. <1> ~ <12> 13. The photocurable composition according to claim 12, <14> For photolithography, <1> ~ <13> 13. The photocurable composition according to claim 12, <15> <1> ~ <14> 2. A cured product of the photocurable composition according to claim 1.

[0011] <16> <15> A dental product comprising a cured product of the photocurable composition according to claim 1. <17> It is a medical device used in the oral cavity. <16> 2. A dental product as described in claim 1. Effect of the Invention

[0012] According to the present disclosure, there is provided a photocurable composition that, after photocuring, has excellent fracture toughness and appropriate ranges of flexural strength and flexural modulus. According to another aspect of the present invention, there is provided a cured product of the photocurable composition, and a dental product comprising the cured product of the photocurable composition. [Brief description of the drawings]

[0013] [Figure 1A] 1 shows the shape of a test piece for a fastening test. [Figure 1B] FIG. 2 is a schematic diagram showing a state in which a detachment test piece is attached to a subject in a detachment test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. In this specification, the term "(meth)acrylic monomer" is a concept that encompasses both acrylic monomers and methacrylic monomers. In addition, in this specification, the term "(meth)acryloyloxy group" is a concept that encompasses both an acryloyloxy group and a methacryloyloxy group, and when written as "acryloyloxy group" or "methacryloyloxy group", it refers only to each of them. As used herein, a "urethane bond" refers to a -NHC(=O)O- bond.

[0015] [Photocurable composition] The photocurable composition according to the present disclosure is a photocurable composition containing a photopolymerizable component and a photopolymerization initiator. The photopolymerizable component preferably contains a di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds, and an acrylic monomer (B) having one acryloyl group.

[0016] The photocurable composition of the present disclosure contains a di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds, an acrylic monomer (B) having one acryloyl group, and a photopolymerization initiator, and thus has excellent fracture toughness and appropriate ranges of flexural strength and flexural modulus after photocuring. Therefore, photo-formed objects produced by photo-forming using the photocurable composition of the present disclosure, and dental products containing the photo-formed objects, also have excellent fracture toughness, and have appropriate ranges of flexural strength, flexural modulus, ease of attachment and removal, and durability when repeatedly attached and removed.

[0017] In this specification, "the ratio of the number of acryloyl groups to the total number of acryloyl groups and methacryloyl groups in the photocurable composition" refers to the number of all acryloyl groups in the photocurable composition divided by the total number of all acryloyl groups and methacryloyl groups, multiplied by 100, and expressed as a percentage.

[0018] In the photocurable composition of the present disclosure, the ratio of the number of acryloyl groups to the total number of acryloyl groups and methacryloyl groups in the photocurable composition is preferably 10% or more. By making it 10% or more, toughness can be improved. From the viewpoint of improving toughness, the ratio of the number of acryloyl groups to the total number of acryloyl groups and methacryloyl groups in the photocurable composition is more preferably 20% or more, even more preferably 30% or more, even more preferably 40% or more, even more preferably 50% or more, 60% or more, even more preferably 70% or more, and particularly preferably 100%.

[0019] The photocurable composition of the present disclosure has a flexural strength (bending strength) in the range of 50 MPa to 100 MPa, a flexural modulus in the range of 1500 MPa to 2500 MPa, and a total work of fracture of 250 J / m 2 When the flexural strength, flexural modulus, and total work of fracture each satisfy the above range, it indicates that the resulting photocured product has excellent toughness and a hardness in an appropriate range.

[0020] If the flexural strength is 50 MPa or more and the flexural modulus is 1500 MPa or more, the cured product of the photocurable composition of the present disclosure has a practically sufficient hardness when used, for example, in dental products.If the flexural strength is 100 MPa or less and the flexural modulus is 2500 MPa or less, the cured product of the photocurable composition of the present disclosure can be used, for example, in medical instruments used in the oral cavity, without causing pain and providing a good usability.

[0021] In the cured product obtained by curing the photocurable composition of the present disclosure, the flexural modulus is more preferably 1500 to 2500 MPa or less, and particularly preferably 2000 MPa or less. Suitable flexural modulus ranges are, for example, 1500 MPa to 2500 MPa, or 1500 MPa to 2000 MPa. The total work of fracture is 250 J / m 2 It is preferable that the total breaking work is 300 J / m or more. By setting the total breaking work in this range, better usability and strength can be obtained. 2 More preferably, it is 400 J / m or more. 2 More preferably, it is 500 J / m or more. 2 It is particularly preferable that the total work of destruction is equal to or greater than 1100 J / m. 2 It is preferable that it is less than 1000 .mu.m. By setting the thickness within the above range, when the medical device is formed into a splint or other medical device to be used in the oral cavity, a good usability can be obtained without causing pain, and the device can be easily removed after attachment. In addition, the flexural modulus is 2500 MPa or less, and the total work of destruction is 250 J / m2 Due to the above, when used in a medical instrument to be used in the oral cavity, it is easy to attach and detach, and has excellent durability when repeatedly attached and detached. As described in ISO 20795-2, a bending strength of 50 MPa or more and a bending modulus of 1500 MPa or more can provide suitable usability, strength, and durability when a cured product of the photocurable composition of the present disclosure is used in, for example, a medical device to be used in the oral cavity.

[0022] The photocurable composition of the present disclosure has a flexural strength (bending strength) in the range of 50 MPa to 70 MPa, a flexural modulus in the range of 1500 MPa to 2000 MPa, and a total work of fracture of 250 J / m 2 More preferably, the total work of destruction is 300 J / m 2 More preferably, it is 400 J / m or more. 2 More preferably, it is 500 J / m or more. 2 It is particularly preferable that the bending modulus is within the above range. When the cured product of the photocurable composition of the present disclosure is used in, for example, a medical device to be used in the oral cavity, pain is unlikely to occur and a better feeling of use can be obtained. By suppressing the bending modulus while maintaining the total work of fracture high, a medical device with excellent feeling of use and excellent strength can be obtained. In addition, by setting the bending modulus and the total work of fracture within the above range, a medical device can be obtained that is easy to attach and detach when used in a medical device to be used in the oral cavity and has excellent durability when repeatedly attached and detached.

[0023] The bending strength and bending modulus of elasticity of the photocurable composition of the present disclosure were measured by forming a shaped object having dimensions of 64 mm × 10 mm × thickness of 3.3 mm, and the bending strength and bending modulus of elasticity of the obtained object were measured by applying a force of 10 J / cm 2 The product is irradiated with ultraviolet light under the above conditions and photocured to produce a photolithographic object (i.e., a cured product; the same applies below). The photolithographic object obtained is then stored in a constant temperature water bath at 37±1°C for 50±2 hours, after which the flexural strength (flexural strength) and flexural modulus are measured in accordance with ISO20795-1:2008 (or JIS T 6501:2012).

[0024] In addition, the total fracture work (J / cm 2 The photocurable composition of the present disclosure is molded into a shape having a size of 39 mm × 8 mm × thickness of 4 mm, and the obtained shape is subjected to a bending test of 10 J / cm 2 The resulting stereolithography was then notched in accordance with ISO20795-1:2008 and stored in a thermostatic water bath at 37±1°C for 7 days±2 hours. After storage, a fracture toughness test was performed using a bending test at a pressing speed of 1.0±0.2mm / min to measure the total fracture work (J / m 2 ) is measured.

[0025] The photocurable composition of the present disclosure is suitable for use in stereolithography. In the present disclosure, "stereolithography" refers to a type of three-dimensional modeling method using a 3D printer. Examples of photolithography methods include the SLA (Stereo Lithography Apparatus) method, the DLP (Digital Light Processing) method, and the inkjet method. The photocurable composition of this embodiment is particularly suitable for SLA or DLP type stereolithography.

[0026] The SLA method includes a method in which a photocurable composition is irradiated with spot-shaped ultraviolet laser light to obtain a three-dimensional object. When dental products and the like are manufactured by the SLA method, for example, the photocurable composition of this embodiment is stored in a container, and the liquid surface of the photocurable composition is selectively irradiated with spot-shaped ultraviolet laser light so as to obtain a desired pattern, thereby curing the photocurable composition, forming a cured layer of a desired thickness on the modeling table, and then the modeling table is lowered, and one layer of liquid photocurable composition is supplied onto the cured layer, and similarly cured, and the lamination operation to obtain a continuous cured layer is repeated. In this way, dental products and the like can be manufactured.

[0027] The DLP method includes a method in which a photocurable composition is irradiated with planar light to obtain a three-dimensional object. For the method of obtaining a three-dimensional object by the DLP method, for example, the descriptions in Japanese Patent No. 5111880 and Japanese Patent No. 5235056 can be referred to as appropriate. When dental products and the like are produced by the DLP method, for example, a lamp that emits light other than laser light, such as a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, or a low-pressure mercury lamp, or an LED, is used as a light source, a planar drawing mask having a plurality of digital micromirror shutters arranged in a planar manner is placed between the light source and the modeling surface of the photocurable composition, and light is irradiated through the planar drawing mask to the modeling surface of the photocurable composition to sequentially laminate cured layers having a predetermined shape pattern. In this way, dental products and the like can be produced.

[0028] An example of the inkjet method is a method in which droplets of a photocurable composition are continuously discharged from an inkjet nozzle onto a substrate, and the droplets attached to the substrate are irradiated with light to obtain a three-dimensional object. When dental products and the like are produced by the inkjet method, for example, a photocurable composition is discharged from the inkjet nozzle onto a substrate while a head equipped with an inkjet nozzle and a light source is scanned in a plane, the discharged photocurable composition is irradiated with light to form a cured layer, and these operations are repeated to sequentially laminate the cured layers, whereby dental products and the like can be produced.

[0029] From the viewpoint of suitability for producing dental products by stereolithography, the photocurable composition of the present disclosure preferably has a viscosity of 20 mPa·s to 5000 mPa·s at 25°C and 50 rpm measured using an E-type viscometer. The lower limit of the viscosity is more preferably 50 mPa·s. The upper limit of the viscosity is more preferably 3000 mPa·s, more preferably 2000 mPa·s, even more preferably 1500 mPa·s, and particularly preferably 1200 mPa·s.

[0030] Next, the components of the photocurable composition of the present disclosure will be described. The photocurable compositions of the present disclosure contain at least one photopolymerizable component. The photopolymerizable component includes a compound containing an ethylenic double bond. Examples of the compound containing an ethylenic double bond include (meth)acrylic monomers, styrene, styrene derivatives, and (meth)acrylonitrile. As the photopolymerizable component, the photopolymerizable components described in paragraphs 0030 to 0059 of WO 2019 / 189652 may be used. The photopolymerizable component preferably contains at least one (meth)acrylic monomer.

[0031] The (meth)acrylic monomer constituting the (meth)acrylic monomer component is not particularly limited as long as it is a monomer having one or more (meth)acryloyl groups in the molecule. The (meth)acrylic monomer may be a monofunctional (meth)acrylic monomer (i.e., a monomer having one (meth)acryloyl group in the molecule), a difunctional (meth)acrylic monomer (i.e., a monomer having two (meth)acryloyl groups in the molecule), or a polyfunctional (meth)acrylic monomer (i.e., a tri- or higher functional (meth)acrylic monomer; i.e., a monomer having three or more (meth)acryloyl groups in the molecule).

[0032] The photopolymerizable component in the photocurable composition of the present disclosure comprises a di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds, It is preferable that the composition contains at least one acrylic monomer (B) having one acryloyl group, and it is more preferable that the composition contains both the di(meth)acrylic monomer (A) and the acrylic monomer (B). When the photopolymerizable component contains at least one (preferably both) of the di(meth)acrylic monomer (A) and the acrylic monomer (B), it is easy to achieve the above-mentioned preferred range of flexural modulus and / or total work of rupture. A method for adjusting the flexural modulus and flexural strength while maintaining the total work of fracture can be to adjust the type and ratio of the acrylic monomer (B). For example, by increasing the aromatic ring concentration of the acrylic monomer (B), the flexural modulus and flexural strength can be increased while maintaining the total work of fracture, and by decreasing the aromatic ring concentration, the flexural modulus and flexural strength can be decreased while maintaining the total work of fracture. In particular, in order to improve the total work of fracture, the aromatic ring concentration of the acrylic monomer (A) can be increased to adjust the total work of fracture. In particular, in order to improve the total work of fracture and adjust the flexural modulus and flexural strength to be low, it is easy to achieve this by increasing the content of the acrylic monomer (B).

[0033] <Di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds> The photocurable composition of the present disclosure preferably contains a di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds. The di(meth)acrylic monomer (A) does not have any (meth)acryloyloxy groups other than the two (meth)acryloyloxy groups. The di(meth)acrylic monomer (A) does not have any urethane bonds other than the two urethane bonds. The di(meth)acrylic monomer (A) may be one type or two or more types, so long as it is a di(meth)acrylic monomer having two (meth)acryloyloxy groups and two urethane bonds.

[0034] The di(meth)acrylic monomer (A) is preferably a compound represented by the following general formula (1).

[0035] [ka] In formula (1), R 1 is a divalent chain hydrocarbon group, a divalent hydrocarbon group having an aromatic structure, or a divalent hydrocarbon group having an alicyclic structure, and R 2 and R 3each independently represents a divalent chain hydrocarbon group which may have a substituent, R 4 and R 5 are each independently a methyl group or a hydrogen atom.

[0036] In formula (1), R 1 R is preferably a divalent hydrocarbon group having an aromatic structure or a divalent hydrocarbon group having an alicyclic structure. 1 By including a ring structure, the viscosity is suppressed, the toughness is improved, and the bending strength and bending modulus are in an appropriate range.

[0037] R in Equation (1) 1 In the above, the number of carbon atoms in the divalent chain hydrocarbon group is preferably 1 to 20, more preferably 1 to 10, and particularly preferably 2 to 6. The divalent chain hydrocarbon group may be linear or branched, saturated or unsaturated, and may have a substituent. It is preferably a linear or branched alkylene group having 1 to 20 carbon atoms, more preferably a linear or branched alkylene group having 1 to 12 carbon atoms, and particularly preferably a linear or branched alkylene group having 1 to 10 carbon atoms.

[0038] Specific examples of the divalent linear or branched alkylene group having 1 to 20 carbon atoms include linear or branched methylene, ethylene, propanediyl, butanediyl, pentanediyl, hexanediyl, heptanediyl, octanediyl, nonanediyl, decanediyl, undecanediyl, dodecanediyl, tridecanediyl, tetradecanediyl, pentadecanediyl, octadecanediyl, eicosylene, vinylene, propenediyl, butenediyl, pentanediyl, ethynylene, propynylene, and 2,4,4-trimethylhexylene groups. Among these, 2,4,4-trimethylhexylene is particularly preferred.

[0039] R in Equation (1) 1In the above, the divalent hydrocarbon group having an aromatic structure is preferably a divalent hydrocarbon group having an aromatic structure having 6 to 20 carbon atoms, which may have a substituent, more preferably having 6 to 12 carbon atoms, and particularly preferably having 6 to 10 carbon atoms. Examples of the divalent hydrocarbon group having an aromatic structure include an arylene group, an alkylenearylene group, an alkylenearylenealkylene group, and an arylenealkylenearylene group. R is a high-fracture material because it has a low viscosity, a moderate bending strength and bending modulus, and a high total work of fracture. 1 is preferably an alkylenearylene group or an alkylenearylenealkylene group.

[0040] Specific examples of the arylene group, alkylenearylene group, alkylenearylenealkylene group, alkylarylene group and arylenealkylenearylene group include a 1,3- or 1,4-phenylene group, a 1,3- or 1,4-phenylenedimethylene group, and a 1,3- or 1,4-phenylenediethylene group.

[0041] R in Equation (1) 1 In the above, the divalent hydrocarbon group having an alicyclic structure preferably has 3 to 20 carbon atoms, more preferably 6 to 12 carbon atoms, and particularly preferably 6 to 8 carbon atoms. Examples of the alicyclic structure include a cyclopropylene group, a cyclobutylene group, a cyclopentylene group, a cyclohexylene group, a cyclohexenylene group, a cycloheptylene group, a cyclooctylene group, a cyclononylene group, a cyclodecylene group, a cycloundecylene group, a cyclododecylene group, a cyclotridecylene group, a cyclotetradecylene group, a cyclopentadecylene group, a cyclooctadecylene group, a cycloicosylene group, a bicyclohexylene group, a norbornylene group, an isobornylene group, and an adamantylene group. Of these, a norbornylene group and an isobornylene group are preferred.

[0042] R 1When is a divalent hydrocarbon group having an alicyclic structure, particularly preferred examples are as follows: * represents a bonding position.

[0043] [ka]

[0044] R in Equation (1) 1 may have a substituent, and examples of the substituent include a straight-chain or branched-chain alkyl group having 1 to 6 carbon atoms.

[0045] R in Equation (1) 1 In the above, the divalent hydrocarbon group having an alicyclic structure is preferably a divalent hydrocarbon group having a structure in which two divalent alkylene groups (e.g., alkylene groups having 1 to 3 carbon atoms), which may be the same or different, are bonded to an alicyclic structure via one of the bonds of each of them (i.e., a structure in which an alicyclic structure is bonded between two divalent alkylene groups), or a divalent hydrocarbon group having a structure in which an alicyclic structure is bonded to one of the bonds of one divalent alkylene group (e.g., an alkylene group having 1 to 3 carbon atoms), and more preferably a divalent hydrocarbon group having an alicyclic structure between two methylene groups or a divalent hydrocarbon group bonded to an alicyclic structure via one of the bonds of one methylene group.

[0046] In formula (1), R 2 and R 3 R is each independently a divalent chain hydrocarbon group which may have a substituent. 2 and R 3 A divalent chain hydrocarbon group suitable for R 1 The divalent chain hydrocarbon groups are the same as those suitable for R 2 and R 3 The carbon number is preferably 2 to 6, and more preferably 2 to 3. From the viewpoint of suppressing the viscosity, the carbon number is preferably 2 to 6 and particularly preferably 2 to 3. In addition, from the viewpoint of suppressing the viscosity, the carbon number is preferably 2 to 6 and the chain hydrocarbon group is preferably unsubstituted, and particularly preferably 2 to 3.

[0047] R 2 and R3 When has a substituent, examples of the substituent include an alkyl group having 1 to 6 carbon atoms, such as a methyl group or an ethyl group; an aryl group; a cycloalkyl group having 3 to 6 carbon atoms, such as a cyclopentyl group or a cyclohexyl group; a tolyl group, a xylyl group, a cumyl group; a styryl group, or an alkoxyphenyl group, such as a methoxyphenyl group, an ethoxyphenyl group, or a propoxyphenyl group.

[0048] Examples of compounds suitable as the di(meth)acrylic monomer (A) include a urethane diacrylic monomer which is a reaction product of one isocyanate selected from the group consisting of m-xylylene diisocyanate, tetramethylxylylene diisocyanate, norbornene diisocyanate, and isophorone diisocyanate with one hydroxyacrylate selected from the group consisting of hydroxyethyl acrylate, hydroxypropyl acrylate, and 4-hydroxybutyl acrylate, and the di(meth)acrylic monomer (A) used in the examples described below.

[0049] The molecular weight of the di(meth)acrylic monomer (A) is preferably 380-700, and more preferably 400-650, in terms of weight average molecular weight.

[0050] The di(meth)acrylic monomer (A) may be synthesized from a commercially available monomer. For example, the di(meth)acrylic monomer (A) may be synthesized from two molecules of hydroxy(meth)acrylate and one molecule of diisocyanate. Examples of suitable hydroxy(meth)acrylates are as follows: In the following structures, "Et" represents an ethyl group.

[0051] [ka]

[0052] Examples of suitable diisocyanates are as follows: In the structures below, "Me" represents a methyl group.

[0053] [ka]

[0054] <Acrylic monomer having one acryloyl group (B)> The photocurable composition of the present disclosure includes an acrylic monomer (B) having one acryloyl group. The acrylic monomer (B) has no acryloyl groups other than the one acryloyl group. The acrylic monomer (B) may be one type or two or more types, so long as it is an acrylic monomer having one acryloyl group.

[0055] The acrylic monomer (B) is preferably a compound represented by the following general formula (2) or (3).

[0056] [ka]

[0057] In formula (2), R 6 is a monovalent organic group which may have a ring structure. In formula (3), R 7 and R 8 each independently represents a monovalent organic group which may have a ring structure or a hydrogen atom; R 7 and R 8 may be bonded to each other to form a ring.

[0058] The acrylic monomer (B) is preferably a compound represented by the general formula (2), R 6 is preferably a monovalent organic group having a ring structure and 3 to 30 carbon atoms, and more preferably a monovalent organic group having a ring structure and 6 to 20 carbon atoms.

[0059] In formula (2), R 6 may be a structure represented by the following general formula (4). *-L 1 -A (4) In formula (4), L 1 represents a single bond or a divalent chain hydrocarbon group having 1 to 30 carbon atoms which may have a heteroatom which is O or N, and A represents a hydrogen atom, a monovalent alicyclic group having 3 to 30 carbon atoms which may have a heteroatom which is O or N, or an aryl group having 6 to 30 carbon atoms. * represents a bonding position.

[0060] In general formula (4), L 1 The divalent chain hydrocarbon group having 1 to 30 carbon atoms and optionally having a heteroatom which is O or N, represented by the following formula, may be linear or branched. L 1 More preferably, the carbon number is 1 to 20, further preferably 1 to 10, and particularly preferably 1 to 8. L 1 When contains a heteroatom, the number of heteroatoms is preferably 1 to 3, and more preferably 1 or 2.

[0061] L 1 L may have a substituent. 1 Suitable examples of the substituent include an alkyl group having 1 to 3 carbon atoms, a hydroxy group, and an alkyl group having 1 to 3 carbon atoms in which one or two hydrogen atoms are substituted with a hydroxy group. L 1 may contain a urethane bond. 1 When the urethane bond is contained, the number of the urethane bond may be one or two.

[0062] L 1 Examples of the above include the following structures: [ka]

[0063] In formula (4), examples of the monovalent alicyclic group represented by A and having 3 to 20 carbon atoms, which may have a heteroatom of O or N, include a cyclopropyl group, a cyclobutyl group, a cyclopentyl group, a cyclohexyl group, a cyclohexenyl group, a cycloheptyl group, a cyclooctyl group, a cyclononyl group, a cyclodecyl group, a cycloundecyl group, a cyclododecyl group, a cyclotridecyl group, a cyclotetradecyl group, a cyclopentadecyl group, a cyclooctadecyl group, a cycloicosyl group, a bicyclohexyl group, a norbornyl group, an isobornyl group, an adamantyl group, a morpholyl group, a piperidino group, a piperazino group, and a dioxane group. The number of carbon atoms in the monovalent alicyclic group is preferably 5 to 12, and more preferably 6 to 10.

[0064] In the formula (4), examples of the aromatic structure in the aryl group having 6 to 30 carbon atoms represented by A include a phenyl structure, a biphenyl structure, a naphthyl structure, and an anthryl structure.

[0065] A may have a substituent. Suitable examples of the substituent of A include an alkyl group having 1 to 6 carbon atoms, such as a methyl group or an ethyl group; a hydroxy group; an alkyl group having 1 to 6 carbon atoms substituted with one or two hydroxy groups; an aryl group; a cycloalkyl group having 3 to 6 carbon atoms, such as a cyclopentyl group or a cyclohexyl group; a tolyl group, a xylyl group, a cumyl group, a styryl group, or an alkoxyphenyl group, such as a methoxyphenyl group, an ethoxyphenyl group, or a propoxyphenyl group.

[0066] Examples of A include the following, where * represents the bonding position.

[0067] [ka]

[0068] The organic group represented by formula (4) preferably has 1-30 carbon atoms in total, and more preferably has 1-20 carbon atoms in total.

[0069] In the general formula (3), R 7 and R 8 each independently represents a monovalent organic group which may have a ring structure or a hydrogen atom; R 7 and R 8 may be bonded to each other to form a ring. Suitable R 7 and R 8 Examples of the alkyl group include monovalent hydrocarbon groups having 1 to 30 carbon atoms which may have a heteroatom which is O or N. The chain hydrocarbon group may be linear or branched, saturated or unsaturated, and may have a substituent. The number of carbon atoms is more preferably 1-20, and further preferably 1-10.

[0070] R 7 and R 8 Examples of the organic group in R include alkyl groups having 1 to 30 carbon atoms, such as methyl, ethyl, and propyl groups, which may have a heteroatom of O or N. 7 and R 8 It is preferable that one of the above is a hydroxyethyl group or a butoxymethyl group, and the other is a hydrogen atom. For example, the following monomers are preferable.

[0071] [ka]

[0072] R 7 and R 8 Examples of the acrylic monomer (B) in which the groups are bonded to each other to form a ring include the following.

[0073] [ka]

[0074] The molecular weight of the acrylic monomer (B) is not particularly limited, but the weight average molecular weight is preferably 80-500, more preferably 100-400, and particularly preferably 130-320.

[0075] Examples of compounds suitable as the acrylic monomer (B) include the compounds used in the examples described below.

[0076] In the photocurable composition of the present disclosure, the content of the di(meth)acrylic monomer (A) is preferably 300 parts by mass or more and 950 parts by mass or less, and more preferably 450 parts by mass or more and 900 parts by mass or less, relative to 1,000 parts by mass in total of the contents of the (meth)acrylic monomer components contained in the photocurable composition. The "total content of (meth)acrylic monomer components" refers to the total content of all monomers having a (meth)acryloyl group or a (meth)acryloyloxy group contained in the photocurable composition of the present disclosure.

[0077] In the photocurable composition of the present disclosure, the total content of the di(meth)acrylic monomer (A) and the acrylic monomer (B) is preferably 800 parts by mass or more, more preferably 900 parts by mass or more, and even more preferably 950 parts by mass or more, per 1000 parts by mass of the total content of the (meth)acrylic monomer components contained in the photocurable composition.

[0078] <Photopolymerization initiator> The photocurable composition of the present disclosure contains a photopolymerization initiator. The photopolymerization initiator is not particularly limited as long as it generates radicals when irradiated with light, but it is preferable that the photopolymerization initiator generates radicals at the wavelength of light used in stereolithography. The wavelength of light used in stereolithography is generally 365 nm to 500 nm, but in practice it is preferably 365 nm to 430 nm, and more preferably 365 nm to 420 nm.

[0079] Examples of photopolymerization initiators that generate radicals at the wavelength of light used in stereolithography include alkylphenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin compounds, acetophenone compounds, benzophenone compounds, thioxanthone compounds, α-acyloxime ester compounds, phenylglyoxylate compounds, benzyl compounds, azo compounds, diphenyl sulfide compounds, organic dye compounds, iron-phthalocyanine compounds, benzoin ether compounds, and anthraquinone compounds. Among these, from the viewpoint of reactivity and the like, alkylphenone compounds and acylphosphine oxide compounds are preferred.

[0080] An example of the alkylphenone compound is 1-hydroxy-cyclohexyl-phenyl-ketone (Omnirad184: manufactured by IGMresins). Examples of the acylphosphine oxide compound include bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide (Omnirad819: manufactured by IGMresins), and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide (OmniradTPO: manufactured by IGMresins).

[0081] The photocurable composition of the present disclosure may contain only one type of photopolymerization initiator, or may contain two or more types. The content of the photopolymerization initiator in the photocurable composition of the present disclosure (the total content when two or more types are used) is preferably 0.1 mass % to 10 mass %, more preferably 0.2 mass % to 5 mass %, and particularly preferably 0.3 mass % to 3 mass %.

[0082] <Other ingredients> The photocurable composition of the present disclosure may contain one or more other components other than the di(meth)acrylic monomer (A), the acrylic monomer (B), and the photopolymerization initiator, as necessary. When the photocurable composition contains the other components, the total mass of the di(meth)acrylic monomer (A), the acrylic monomer (B) and the photopolymerization initiator is preferably 30 mass% or more, more preferably 50 mass% or more, even more preferably 70 mass% or more, still more preferably 80 mass% or more, even more preferably 90 mass% or more, and particularly preferably 95 mass% or more, based on the total amount of the photocurable composition.

[0083] Examples of the other components include monomers other than the di(meth)acrylic monomer (A) and the acrylic monomer (B). When the photocurable composition contains a monomer other than the di(meth)acrylic monomer (A) and the acrylic monomer (B) as other components, the content of the monomer as the other component is preferably 50% or less, more preferably 30% or less, even more preferably 20% or less, and particularly preferably 10% or less, based on the total mass of the di(meth)acrylic monomer (A) and the acrylic monomer (B). The lower limit of the content of the monomer as the other component is not particularly limited, and may be 0%.

[0084] Examples of other components include colorants, monomers other than di(meth)acrylic monomers and (meth)acrylic monomers, coupling agents such as silane coupling agents (e.g., 3-acryloxypropyltrimethoxysilane), additives such as rubber agents, ion trapping agents, ion exchange agents, leveling agents, plasticizers, and defoaming agents, and thermal polymerization initiators. When the photocurable composition of the present disclosure contains a thermal polymerization initiator, photocuring and thermal curing can be performed in combination. Examples of the thermal polymerization initiator include a thermal radical generator and an amine compound.

[0085] The method for preparing the photocurable composition of the present disclosure is not particularly limited, and examples thereof include a method in which the di(meth)acrylic monomer (A), the acrylic monomer (B), and the photopolymerization initiator (and other components as necessary) are mixed. The means for mixing the components is not particularly limited, and includes, for example, ultrasonic dissolution, a twin-arm mixer, a roll kneader, a twin-screw extruder, a ball mill kneader, and a planetary mixer. The photocurable composition of this embodiment may be prepared by mixing the components, filtering the mixture through a filter to remove impurities, and then subjecting the mixture to a vacuum degassing treatment.

[0086] [Photocured product] The method of photocuring using the photocurable composition of the present disclosure is not particularly limited, and any known method and device can be used. For example, a method of laminating multiple cured layers by repeating a process of forming a thin film made of the photocurable composition of the present disclosure and a process of irradiating the thin film with light to obtain a cured layer multiple times to produce a photocured product of a desired shape can be mentioned. The obtained photocured product may be used as it is, or may be used after further performing post-cure by light irradiation, heating, etc. to improve its mechanical properties, shape stability, etc.

[0087] Furthermore, the glass transition temperature (Tg) of the photocurable composition of the present disclosure after photocuring is not particularly limited, but from the viewpoints of flexural strength and flexural modulus, the glass transition temperature (Tg) after photocuring is preferably 70°C or higher, and more preferably 80°C or higher. From the viewpoint of fracture toughness, the glass transition temperature (Tg) after photocuring is preferably 140° C. or lower.

[0088] [Dental products] The dental product containing the cured product of the photocurable composition of the present disclosure (i.e., photo-molded product) is not particularly limited, and can be used in artificial teeth, prostheses, medical instruments used in the oral cavity, etc., but is preferably a medical instrument used in the oral cavity, and is particularly preferably a mouthpiece. It is preferable to use the cured product of the photocurable composition of the present disclosure as at least a part of the dental product. Examples of medical instruments used in the oral cavity include a mouthpiece for orthodontic treatment, a splint such as a splint for adjusting occlusion or a splint for treating temporomandibular joint disorder, and a mouthpiece for treating sleep apnea syndrome. By using the cured product of the photocurable composition of the present disclosure, it is possible to manufacture a medical device that is excellent in usability when used in the oral cavity and has sufficient strength and hardness. Furthermore, when it is formed into a medical device to be used in the oral cavity, such as a splint, it is possible to easily put on and take off the device and to improve durability when it is repeatedly put on and taken off. EXAMPLES

[0089] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0090] [Examples 1 to 28, Comparative Examples 1 to 12] <Preparation of Photocurable Composition> The components shown in the following Tables 1-1 to 1-6 were mixed to obtain photocurable compositions.

[0091] <Measurement and Evaluation> The photocurable compositions thus obtained were subjected to the following measurements and evaluations, and the results are shown in Tables 1-1 to 1-6.

[0092] (Viscosity of Photocurable Composition) The viscosity of the photocurable composition was measured at 25° C. and 50 rpm using an E-type viscometer.

[0093] (Bending strength and bending modulus of elasticity of stereolithography) The obtained photocurable composition was shaped into a shape having a size of 64 mm × 10 mm × thickness of 3.3 mm using a 3D printer (Kulzer, Cara Print 4.0) to obtain a shaped object. The obtained shaped object was irradiated with ultraviolet light having a wavelength of 365 nm at 10 J / cm. 2 The resin was irradiated under the above conditions for full curing to obtain a stereolithography object. The obtained stereolithography (hereinafter referred to as "test piece") was stored in a thermostatic water bath at 37±1° C. for 50±2 hours. Thereafter, the test piece was removed from the thermostatic water bath, and the flexural strength and flexural modulus of the test piece were measured in accordance with ISO20795-1: 2008. These measurements were performed using a universal testing machine (manufactured by Intesco Corporation) at a test speed of 5±1 mm / min.

[0094] (Total work of fracture in fracture toughness testing by bending test) The obtained photocurable composition was shaped into a shape having a size of 39 mm × 8 mm × thickness of 4 mm using a 3D printer (Kulzer, Cara Print 4.0) to obtain a shaped object. The obtained shaped object was irradiated with ultraviolet light having a wavelength of 365 nm at 10 J / cm. 2 The object was cured completely by irradiation under the above conditions to obtain a photo-fabricated object. The obtained stereolithography (hereinafter referred to as "test piece") was notched in accordance with ISO20795-1:2008, and stored in a constant temperature water bath at 37±1°C for 7 days±2 hours. The test specimen was then removed from the thermostatic bath and subjected to a fracture toughness test using a bending test in accordance with ISO20795-1:2008 to determine the total fracture work (J / m 2 The fracture toughness test by bending test (i.e., measurement of total work of fracture) was performed using a universal testing machine (manufactured by Intesco Co., Ltd.) at a pressing speed of 1.0±0.2 mm / min.

[0095] (Attachment / detachment evaluation) Detachable test using detachable test piece The obtained photocurable composition was shaped into a shape shown in FIG. 1A with a thickness of 2 mm using a 3D printer (Kulzer, Cara Print 4.0), to obtain a shaped object. The obtained shaped object was irradiated with ultraviolet light having a wavelength of 365 nm at 10 J / cm. 2 The object was cured completely by irradiation under the above conditions to obtain a photo-fabricated object. The obtained stereolithography (hereinafter referred to as "test piece") was attached to the detachable object as shown in Figure 1B using a universal testing machine (manufactured by Intesco Co., Ltd.), and the test piece was moved up and down at a moving speed of 120.0 ± 2.0 mm / min to evaluate the attachment and detachment. The detachable object was created by cutting a SUS304 cylinder with a diameter of 10 mm so that the chord length of the circular cross section was 7.07 mm. During the test, the cut surface was placed as the ground surface. After 10,000 up and down movements, the test piece was observed and rated as "A" if there was no change in shape and no cracks after the test, "B" if there was a change in shape and no cracks after the test, and "C" if cracks occurred after the test. 1A and 1B, T represents thickness, D2 represents the diameter of the semicircle, H1 and H2 represent the height of the indicated portion, and W1 and W2 represent the width of the indicated portion. In Fig. 1B, D1 represents the diameter of the cross section of the cylinder before the contact surface to be attached / detached is cut, θ represents the angle of the apex of the triangle formed by connecting the center of the circle of the cross section of the cylinder to both ends of the contact surface, and W3 represents the width of the contact surface. T = 2 mm, D1 = 10 mm, D2 = 2 mm, W1 = 15 mm, W2 = 2 mm, W3 = 7.07 mm, H1 = 12 mm, H2 = 5 mm, and θ = 135°. The depth of the test piece shown in Figures 1A and 1B is 10 mm.

[0096] [Table 1-1]

[0097] [Table 1-2]

[0098] [Table 1-3]

[0099] [Table 1-4]

[0100] [Table 1-5]

[0101] [Table 1-6]

[0102] In Tables 1-1 to 1-6, the numbers in the "Composition" column for each Example and Comparative Example are shown in parts by mass. In Tables 1-1 to 1-6, the numbers in the column "Number of acryloyl groups (%)" in each Example and Comparative Example indicate the ratio (%) of the number of acryloyl groups to the total number of acryloyl groups and methacryloyl groups in the photocurable composition.

[0103] <Di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds> The structures of the di(meth)acrylic monomers (A) having two (meth)acryloyloxy groups and two urethane bonds shown in Tables 1-1 to 1-6 are as follows.

[0104] [ka]

[0105] AH-600 is a urethane acrylic monomer manufactured by Kyoeisha Chemical Co., Ltd. UDA, UDMA, MMD-352, KRM-076, and KRM-077 were produced as follows. The abbreviations used in the following Production Examples are explained below. HEA: Hydroxyethyl acrylate TMHDI: 2,4,4-trimethylhexane diisocyanate DBTDL: Dibutyltin dilaurate MEHQ: 4-Methoxyphenol XDI: m-xylylene diisocyanate NBDI: Norbornene diisocyanate

[0106] [Production Example 1: Production of UDA] In a 1-liter 4-neck flask equipped with a thoroughly dried stirring blade and a thermometer, 372 g (3.20 mol) of HEA, 0.71 g of DBTDL (0.1 wt % relative to the total weight of HEA and TMHDI), and 0.35 g of MEHQ (0.05 wt % relative to the total weight of HEA and TMHDI) were added, stirred until homogenous, and then heated to 60°C. Next, 337 g (1.60 mol) of TMHDI was added dropwise over 1 hour. During the dropwise addition, the internal temperature rose due to the heat of reaction, so the amount added was controlled so that it would be below 80°C. After the entire amount was added dropwise, the reaction temperature was kept at 80°C and the reaction was carried out for 10 hours. At this time, the progress of the reaction was tracked by HPLC analysis to confirm the end point of the reaction. 680 g of urethane acrylate (UDA) was obtained by discharging the product from the reactor. The viscosity at 25°C was 7100 mPa·s.

[0107] [Production Example 2: Production of UDMA] In a 1-liter 4-neck flask equipped with a thoroughly dried stirring blade and a thermometer, 416 g (3.20 mol) of HEMA (structure will be described later), 0.75 g of DBTDL (0.1 wt % relative to the total weight of HEMA and TMHDI), and 0.38 g of MEHQ (0.05 wt % relative to the total weight of HEMA and TMHDI) were added, stirred until homogeneous, and then heated to 60°C. Next, 337 g (1.60 mol) of TMHDI was added dropwise over 1 hour. During the dropwise addition, the internal temperature rose due to the reaction heat, so the amount added was controlled so that it would be below 80°C. After the entire amount was added dropwise, the reaction temperature was kept at 80°C and the reaction was carried out for 10 hours. At this time, the progress of the reaction was tracked by HPLC analysis to confirm the end point of the reaction. 720 g of urethane methacrylate (UDMA) was obtained by discharging the product from the reactor. The viscosity at 25°C was 8200 mPa·s.

[0108] [Production Example 3: Production of MMD-352] In a 1-liter 4-neck flask equipped with a thoroughly dried stirring blade and a thermometer, 444 g (2.00 mol) of M-600A, 0.63 g of DBTDL (0.1 wt % relative to the total weight of M-600A and XDI described below), and 0.32 g of MEHQ (0.05 wt % relative to the total weight of M-600A and XDI described below) were added, stirred until homogenous, and then heated to 60°C. Next, 188 g (1.00 mol) of XDI was added dropwise over 1 hour. During the dropwise addition, the internal temperature rose due to the reaction heat, so the amount of dropwise addition was controlled so that it would be 80°C or less. After the entire amount was added dropwise, the reaction temperature was kept at 80°C and the reaction was carried out for 10 hours. At this time, the progress of the reaction was tracked by HPLC analysis to confirm the end point of the reaction. By discharging the product from the reactor, 600 g of urethane acrylate (MMD-352) was obtained. The viscosity at 65°C was 6210 mPa·s.

[0109] [Production Example 4: Production of KRM-076] In a 1-liter 4-neck flask equipped with a thoroughly dried stirring blade and a thermometer, 418 g (3.21 mol) of 2HPA (structure will be described later), 0.72 g of DBTDL (0.1 wt % relative to the total weight of 2HPA and XDI), and 0.36 g of MEHQ (0.05 wt % relative to the total weight of 2HPA and XDI) were added, stirred until homogenous, and then heated to 60 ° C. Then, 303 g (1.61 mol) of XDI was added dropwise over 1 hour. During the dropwise addition, the internal temperature rose due to the reaction heat, so the amount of dropwise addition was controlled so that it would be 80 ° C or less. After the entire amount was added dropwise, the reaction temperature was kept at 80 ° C and the reaction was carried out for 10 hours. At this time, the progress of the reaction was tracked by HPLC analysis to confirm the end point of the reaction. By discharging the product from the reactor, 690 g of urethane acrylate (KRM-076) was obtained. The viscosity at 65 ° C was 570 mPa s.

[0110] [Production Example 5: Production of KRM-077] In a 1-liter 4-neck flask equipped with a thoroughly dried stirring blade and a thermometer, 372 g (3.20 mol) of HEA, 0.70 g of DBTDL (0.1 wt % relative to the total weight of HEA and NBDI), and 0.35 g of MEHQ (0.05 wt % relative to the total weight of HEA and NBDI) were added, stirred until homogenous, and then heated to 60°C. Next, 330 g (1.60 mol) of NBDI was added dropwise over 1 hour. During the dropwise addition, the internal temperature rose due to the heat of reaction, so the amount added was controlled so that it would be below 80°C. After the entire amount was added dropwise, the reaction temperature was kept at 80°C and the reaction was carried out for 10 hours. At this time, the progress of the reaction was tracked by HPLC analysis to confirm the end point of the reaction. 670 g of urethane acrylate (KRM-077) was obtained by discharging the product from the reactor. The viscosity at 65°C was 930 mPa·s.

[0111] <(Meth)acrylic monomer not corresponding to di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds> In Tables 1-1 to 1-6, EBECRYL4100 and EBECRYL4740 are urethane acrylates manufactured by Daicel-Allnex Corporation. Although the details of their structures have not been disclosed, Daicel-Allnex Corporation has disclosed that they are trifunctional, and they have the functional groups shown in Table 2. UA-306T and UA-306H are manufactured by Kyoei Chemical Co., Ltd. The structures of UA-306T and UA-306H are shown below.

[0112] [ka]

[0113] Table 2 shows the numbers of methacryloyloxy groups, acryloyloxy groups and acryloyl groups in one molecule of the above di(meth)acrylic monomer (A) and (meth)acrylic monomers other than di(meth)acrylic monomer (A).

[0114] [Table 2]

[0115] <Acrylic monomer having one acryloyl group (B)> The structures of the acrylic monomers (B) having one acryloyl group shown in Tables 1-1 to 1-6 are as follows.

[0116] [ka]

[0117] [ka]

[0118] IB-XA, POB-A, PO-A, M-600A, and HOP-A are manufactured by Kyoeisha Chemical Co., Ltd. A-LEN-10 is manufactured by Shin-Nakamura Chemical Co., Ltd. ACMO is manufactured by KJ Chemicals Co., Ltd. Photomer4184 is manufactured by IGM Resins Co., Ltd. SR531 is manufactured by Arkema Inc. FA511AS is manufactured by Hitachi Chemical Co., Ltd. M-110 is manufactured by Toagosei Co., Ltd. CHDMMA is manufactured by Nippon Kasei Co., Ltd.

[0119] <Acrylic monomer (B) having one acryloyl group and monomer other than the above-mentioned di(meth)acrylic monomer (A)> In Tables 1-1 to 1-6, 4EG, 4EG-A, HEMA and PO are manufactured by Kyoeisha Chemical Co., Ltd. ABE-300 is manufactured by Shin-Nakamura Chemical Co., Ltd. The structures of each are as follows: [ka]

[0120] Table 3 shows the number of acryloyl groups in one molecule of the acrylic monomer (B) having one acryloyl group, and the acrylic monomer not corresponding to the acrylic monomer (B) or the di(meth)acrylic monomer (A).

[0121] [Table 3]

[0122] <Photopolymerization initiator> The structures of the photopolymerization initiators listed in Tables 1-1 to 1-6 are as follows.

[0123] [ka]

[0124] Omnirad819 (acylphosphine oxide compound), Omnirad184 (alkylphenone compound) and OmniradTPO (acylphosphine oxide compound) are manufactured by IGM Resins.

[0125] As shown in Tables 1-1 to 1-6, the photocurable compositions of the examples containing a di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds, and an acrylic monomer (B) having one acryloyl group were superior overall in bending strength, bending modulus, and total work of fracture, compared with the photocurable compositions of the comparative examples not containing these monomers. For example, it was found that the photocurable compositions of the examples containing an acrylic monomer (B) having one acryloyl group had superior total fracture work compared to photocurable compositions containing a monomer having one methacryloyl group (e.g., Comparative Example 1 and Comparative Example 10).

[0126] In addition, when Example 5, which used UDA as the di(meth)acrylic monomer (A), and Example 13, which used UDMA, were compared, the total work of fracture was superior in Example 5. This shows that the use of acrylate as the di(meth)acrylic monomer (A) provides superior toughness compared to methacrylate.

[0127] In addition, examples containing ACMO or HPA as the acrylic monomer (B) (e.g., Example 1, Example 9, etc.) tended to have high total work of fracture. However, although not shown in the table, these examples tended to have high water absorption due to the high content of ACMO or HPA, etc. In contrast, examples using monofunctional acrylic monomers having a ring structure as the acrylic monomer (B) such as POB-A (e.g., Examples 4, 7, etc.) or examples using them in combination (e.g., Example 10, etc.) were able to obtain appropriate bending strength, bending modulus, and total work of fracture while suppressing water absorption.

[0128] In addition, in the examples (e.g., Example 16) containing AH600 and MMD-352 as the di(meth)acrylic monomer (A), the total work of fracture tended to be high, but the viscosity also tended to be high. In contrast, in the examples (Examples 24, 26, and 27) using a monomer having a ring structure in the center and an alkylene structure, such as KRM-076 or KRM-077, as the di(meth)acrylic monomer (A), it was possible to obtain a high total work of fracture while suppressing the viscosity and having a moderate bending strength and bending modulus.

[0129] In addition, when used as a medical device such as a splint to be used in the oral cavity, a certain degree of hardness and toughness is required, but on the other hand, if the bending strength is too high, the patient is likely to feel pain. From this viewpoint, in some embodiments, the bending strength is kept within the range of 50 to 70 MPa, and the bending strength is set to 250 J / m 2 or more (and in some embodiments, 500 J / m 2 It was found that excellent total fracture work (above) could be obtained and that the material is suitable for medical instruments to be used in the oral cavity.

[0130] When used as a medical device such as a splint for intraoral use, it is required to be repeatedly put on and taken off in the oral cavity, and it is required to be easy to put on and take off, and to have high durability against repeated putting on and taking off. In the examples, the evaluation results of the fastening test were good. Comparative Examples 2 and 3 also showed good evaluation results in the fastening test, but the bending strength was less than 50 MPa and the bending modulus was less than 1500 MPa, which did not satisfy the standards stipulated in ISO-20795-2, and it is considered that the strength is insufficient for medical devices to be used in the oral cavity.

[0131] The disclosure of Japanese Patent Application No. 2019-068556, filed on March 29, 2019, is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described herein are incorporated herein by reference to the same extent as if each individual document, patent application, and technical standard was specifically and individually indicated to be incorporated by reference. The foregoing description of exemplary embodiments of the present invention has been provided for purposes of illustration and description, and is not intended to be exhaustive or to limit the invention to the precise forms disclosed. Obviously, many modifications or variations will be apparent to those skilled in the art. The above embodiments were selected and described in order to best explain the principles and practical applications of the invention and to enable others skilled in the art to understand the invention with various embodiments and various modifications as suitable for the particular use envisaged. It is intended that the scope of the present invention be defined by the following claims and their equivalents.

Claims

1. A di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds and represented by the following general formula (1): an acrylic monomer (B) having one acryloyl group; A photocurable composition comprising: the content of the di(meth)acrylic monomer (A) is 300 parts by mass or more and 950 parts by mass or less, relative to 1000 parts by mass of the total content of the (meth)acrylic monomer components contained in the photocurable composition; a content of monomers other than the di(meth)acrylic monomer (A) and the acrylic monomer (B) being 50% or less based on a total mass of the di(meth)acrylic monomer (A) and the acrylic monomer (B), the photocurable composition being for photolithography. 【Chemistry 1】 (In formula (1), R 1 is a divalent hydrocarbon group having an aromatic structure or a divalent hydrocarbon group having an alicyclic structure, R 2 and R 3 each independently represents a divalent chain hydrocarbon group which may have a substituent, R 4 and R 5 are each independently a methyl group or a hydrogen atom.

2. A di(meth)acrylic monomer (A) having two (meth)acryloyloxy groups and two urethane bonds and represented by the following general formula (1): an acrylic monomer (B) having one acryloyl group; A photocurable composition comprising: the total content of the di(meth)acrylic monomer (A) and the acrylic monomer (B) is 800 parts by mass or more relative to 1000 parts by mass of the total content of the (meth)acrylic monomer components contained in the photocurable composition; a content of the di(meth)acrylic monomer (A) is 300 parts by mass or more and 950 parts by mass or less, relative to 1,000 parts by mass of a total content of (meth)acrylic monomer components contained in the photocurable composition, and the photocurable composition is for photolithography. 【Chemistry 2】 (In formula (1), R 1 is a divalent hydrocarbon group having an aromatic structure or a divalent hydrocarbon group having an alicyclic structure, R 2 and R 3 each independently represents a divalent chain hydrocarbon group which may have a substituent, R 4 and R 5 are each independently a methyl group or a hydrogen atom.

3. 2. The photocurable composition according to claim 1, wherein the total content of the di(meth)acrylic monomer (A) and the acrylic monomer (B) is 800 parts by mass or more per 1000 parts by mass of the total content of the (meth)acrylic monomer components contained in the photocurable composition.

4. 4. The photocurable composition according to claim 1, wherein the ratio of the number of acryloyl groups to the total number of acryloyl groups and methacryloyl groups in the photocurable composition is 10% or more.

5. The cured product obtained by curing the photocurable composition has a bending strength of 50 to 70 MPa, a bending modulus of elasticity of 1500 to 2000 MPa, and a total work of fracture of 250 J / m 2 The photocurable composition according to any one of claims 1 to 4.

6. In the general formula (1), R 1 is a divalent hydrocarbon group having 6 to 12 carbon atoms and an aromatic structure or a divalent hydrocarbon group having 6 to 12 carbon atoms and an alicyclic structure, R 2 and R 3 wherein each independently represents an unsubstituted divalent chain hydrocarbon group having 2 to 6 carbon atoms.

7. The photocurable composition according to any one of claims 1 to 6, wherein the acrylic monomer (B) contains at least one of a compound represented by the following general formula (2) and a compound represented by the following general formula (3): 【Chemistry 3】 (In formula (2), R 6 is a monovalent organic group which may have a ring structure. In formula (3), R 7 and R 8 are each independently a monovalent organic group which may have a ring structure or a hydrogen atom, R 7 and R 8 may be bonded to each other to form a ring.)

8. The acrylic monomer (B) contains a compound represented by general formula (2), In the general formula (2), R 6 The photocurable composition according to claim 7, wherein is a monovalent organic group having a ring structure and having 6 to 20 carbon atoms.

9. The photocurable composition according to any one of claims 1 to 8, wherein the di(meth)acrylic monomer (A) has a weight average molecular weight of 380 to 700.

10. The photocurable composition according to any one of claims 1 to 9, wherein the acrylic monomer (B) has a weight average molecular weight of 130 to 320.

11. The photocurable composition according to any one of claims 1 to 10, having a viscosity of 20 mPa·s to 3000 mPa·s at 25°C and 50 rpm measured using an E-type viscometer.

12. A cured product of the photocurable composition according to any one of claims 1 to 11.

13. A dental product comprising the cured photocurable composition of claim 12.

14. 14. The dental product according to claim 13, which is a medical device for use in the oral cavity.

Citation Information

Patent Citations

  • Ultrahigh-elasticity photocured temporary resin composition as well as preparation method and application thereof

    CN109517105A

  • Curable composite, composite filler, and restorative dental material

    JP1996311115A

  • Photocurable resin composition

    JP2006028499A

  • Manufacturing method of dental prosthesis

    KR101957204B1

  • Novel compound, composition containing said compound, and cured product

    WO2012157568A1

Cited By

  • Photocurable composition, cured product, and dental product

    JP2024050851A

  • Photocurable composition, cured product, and dental product

    US12565555B2